(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
Donkeys in Sudan have been used for different purposes, among which income generation in Khartoum State is the main stay. This Study was conducted to evaluate the role of donkeys in income generation and to examine the impact of endoparasites on the income generation together with the association between endoparasites, daily income and some selected measures. The study revealed that the average daily income was SDG 20.00±15.00 and the most frequent income was SDG 15.00 per day per donkey. There was a significant (P < 0.05) negative correlation between the daily income and infection with gastrointestinal parasites. A significant (P < 0.05) positive correlation between the daily income and the use of anthelmintics was also revealed. The correlation between the daily income and blood parasites was insignificant(P < 0.05) . The daily income has a significant (P < 0.05) positive correlation with the Body Condition Score (BCS) and The Pack cell Volume (PCV %). The relationship between the daily income and the age, body weight and health status and working ability is insignificant (P > 0.05). The study concluded that donkeys play an important role as a mean of income generation in Khartoum state and that gastrointestinal parasites do adversely affect the income generation and recommended rising the awareness of donkeys’ owners on the importance of deworming